SYNTHESIS AND OPTIMIZATION OF GEMCITABINE-LOADED MIL-101NH2 (Fe) NANOCARRIERS: RESPONSE SURFACE METHODOLOGY APPROACH: GEMCITABINE LOADED MIL-101 NH2 (Fe) NANOCARRIERS - PREETI KUSH,; JITENDER MADAN,; PARVEEN KUMAR, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the present study is to synthesize and optimize gemcitabine (GEM)-loaded MIL-101NH2 (Fe) nanocarriers. The design of experiments is used to optimize the formulation for higher encapsulation efficiency (EE) for effective drug delivery. Materials and Methods: MIL-101NH2 (Fe) was synthesized by microwave-assisted hydrothermal method. Central composite design (CCD) under response surface methodology was used for the optimization of GEM encapsulation into the MIL-101NH2 (Fe). The most influential variable that affects the EE was investigated by Perturbation plot. Validation of the design was carried out by performing the experiments under optimal conditions. Further optimized formulation was physicochemically characterized for particle size, surface charge, and surface morphology using zetasizer and scanning electron microscopy (SEM), respectively. Structural integrity of the optimized formulation was carried out by Powder X ray crystallography (PXRD). Fourier-transform infrared (FTIR) spectroscopy was used for the confirmation of GEM loading. Accelerated storage stability analysis was also performed to find out the related parameters. Results: Here in this work, crystalline MIL-101NH2 (Fe) has been successfully synthesized by microwave radiation method. The optimization result revealed that process variables such as GEM concentration, pH, and time significantly affect the desired constraint, EE. Perturbation plot evidenced that among all the variables, pH is the most significant factor followed by drug concentration and time. The optimized formulation exhibited 76.4 ± 7% EE and average particle size of 252.9 ± 9.23 nm. PXRD and SEM results demonstrated that the optimized formulation was crystalline in nature. FTIR spectroscopy confirms the presence of drug inside the MIL-101NH2 (Fe). In vitro release profile revealed that MIL-101NH2 (Fe)-GEM exhibited the sustained release up to 72 h in comparison to the native GEM. Storage-stability studies also indicate that MIL-101NH2 (Fe)-GEM has a shelf life of 6 months. Conclusion: The EE of GEM in MIL-101NH2 (Fe) can be altered by varying the drug concentration and pH during the impregnation.